THE EFFECT OF OWNERSHIP STRUCTURE ON FIXED ASSETS REVALUATION WITH TAX INCENTIVES AS MODERATING VARIABLES - Muhammad Syafiqurrahman; Doddy Setiawan; Sri Suranta; Djoko Suhardjanto (JAFFA, 2018)
This study aims to determine the effect of ownership structure on fixed assets revaluation with tax incentives as a moderate variable. The ownership structure is indicated by firm size, fixed assets intensity, price ratio to book value and leverage. The data used in this study is secondary data obtained from the annual report of companies listed in Indonesia Stock Exchange (IDX) which amounted to 198 manufacturing companies in 2014 and 2015. This research uses sampling method that is purposive sampling with logistic analysis model. The results of this study indicate that firm size, fixed asset intensity, and leverage have no effect on fixed assets revaluation, while price ratio to book value negatively affects fixed asset revaluation. In addition, tax incentives are not a moderate variable.